2009
DOI: 10.1097/ccm.0b013e31819ef9e1
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency percussive ventilation improves perioperatively clinical evolution in pulmonary resection*

Abstract: Under the present settings, HFPV improved oxygenation in one-lung ventilation during pulmonary resection. Postoperatively, it decreased the length of stay and increased the removal of secretions in comparison with CPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Toussaint et al 1 reported significantly better secretion clearance (ie, a 40% increase in sputum weight) with IPV in a small randomized crossover trial in patients with Duchenne muscular dystrophy and excessive sputum production. Similar findings of significantly improved postoperative sputum production also were reported by Lucangelo et al 13 when IPV was applied to patients undergoing pulmonary resection. Although total postoperative sputum production was not different between treatment groups, patients treated with IPV cleared a greater amount of secretions more rapidly (ie, 72% of their total sputum was cleared by the fourth postoperative day, compared to 46% in the group managed with CPAP).…”
Section: Intrapulmonary Percussive Ventilationsupporting
confidence: 88%
“…Toussaint et al 1 reported significantly better secretion clearance (ie, a 40% increase in sputum weight) with IPV in a small randomized crossover trial in patients with Duchenne muscular dystrophy and excessive sputum production. Similar findings of significantly improved postoperative sputum production also were reported by Lucangelo et al 13 when IPV was applied to patients undergoing pulmonary resection. Although total postoperative sputum production was not different between treatment groups, patients treated with IPV cleared a greater amount of secretions more rapidly (ie, 72% of their total sputum was cleared by the fourth postoperative day, compared to 46% in the group managed with CPAP).…”
Section: Intrapulmonary Percussive Ventilationsupporting
confidence: 88%
“…It may also ventilate some alveoli otherwise not reached by the primary tidal volume [20]. We chose a pulsatile frequency of 500 cycles/min because it represents a good compromise between convection of gases at low percussion frequencies (180–240 cycles/min) and gas diffusion at a high oscillation (300–600 cycles/min), a phenomenon that may be linked to the increased kinetics of the oxygen molecules [13]. This high pulsatile frequency does not introduce a bias in the measurement since the P aw is similar to the mean alveolar pressure at frequencies of 5 and 10 Hz [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the two groups behaved differently, as depicted in figure 2. The improvement in Pa o 2 /Fi o 2 could be explained by three findings: (a) respiratory system compliance increased between baseline and 1 h after HFPV, possibly indicating an improvement in respiratory mechanics, which could suggest a certain degree of lung recruitment and improved ventilation/perfusion relationship (from the mechanical point of view HFPV has been reported to increase the C rs and decrease the work of breathing [30]); (b) our group described an increased lung secretion clearance, which was prolonged after the end of treatment [13], and (c) HFPV accommodates volume distribution without overinflating compartments with low time constants, thus presenting a potential beneficial behavior in mechanically heterogeneous lungs [31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIV can enhance oxygenation and minute ventilation via two mechanisms, namely respiratory muscle unloading during inspiration and an increase in tidal volume associated with an increase in alveolar ventilation [21]. High-frequency percussive ventilation has been shown to significantly improve the PaO 2 /FiO 2 ratio in several categories of patients, including burn patients [26], obese patients with compression atelectasis [27], patients with acute respiratory distress syndrome [9,28], newborns [9], tracheotomised patients [29], and postoperative patients [30].…”
Section: Respiratory Rate and Gas Exchangementioning
confidence: 99%